Impact of tannery effluent on Sorghum bicolor (L.) Moench - Sangeetha, V.; Sharavannan, P.S. (Current Botany, 2021)
The present study is aimed to investigate the effect of tannery effluent on different varieties of Sorghum bicolor. The disparate concentrations of tannery effluent viz., 5, 25, 50, 75 and 100% were tested for its impacts on six varieties of Sorghum bicolor (L.) Moench (TNAU CO 5, TNAU CO 30, CO (S) 28, BSR 1, K Tall and Paiyur 1). The experimentation was carried out in a completely randomized design (CRD) with five replications. The impact of tannery effluent on the germination percentage, shoot length (cm), root length (cm), seedling weight (g), vigour index, tolerance index and phytotoxicity were recorded. The outcome revealed that the parameters escalated in 5% effluent concentration and declined after 25% concentration of tannery effluent.